Selected essays on the history of Scots law. John W. Cairns. - Cairns, John W. (Edinburgh studies in law ;, 2015)
A collection of the most influential essays on Legal History from the career of John W. Cairns .The first volume of two, this collection of essays on Scots Law represents a selection of the most cited articles published by Professor John W. Cairns over a distinguished career in Legal History. It is a mark of his international eminence that much of his prolific output has been published outside of the UK, in a wide variety of journals and collections. The consequence is that some of his most valuable writing has appeared in sources which are difficult to locate. This collection covers the foundation and continuity of Scots Law from 16th and 17th century Scotland through the 18th century influence of Dutch Humanism into the 19th century and the further development of the Scots legal system and profession."